Cohomology in 3D Magneto-Quasistatics Modeling (Communications in Computational Physics, 2014)
Electromagnetic modeling provides an interesting context to present a linkbetween physical phenomena and homology and cohomology theories. Over the pasttwenty-five years, a considerable effort has been invested by the computational electromagnetics community to develop fast and general techniques for defining potentials. When magneto-quasi-static discrete formulations based on magnetic scalar potential are employed in problems which involve conductive regions with holes, cuts areneeded to make the boundary value problem well defined. While an intimate connection with homology theory has been quickly recognized, heuristic definitions of cutsare surprisingly still dominant in the literature.The aim of this paper is first to survey several definitions of cuts together with theirshortcomings. Then, cuts are defined as generators of the first cohomology group overintegers of a finite CW-complex. This provably general definition has also the virtueof providing an automatic, general and efficient algorithm for the computation of cuts.Some counter-examples show that heuristic definitions of cuts should be abandoned.The use of cohomology theory is not an option but the invaluable tool expressly neededto solve this problem.